HGG-14. Molecular characterization of unique biological subgroups among H3 wild type high-grade gliomas. (3rd June 2022) - Vanova, Katerina; Krskova, Lenka; Vicha, Ales; Sumerauer, David; Zamecnik, Josef; Koblizek, Miroslav; Libý, Petr; Benes, Vladimir; Malinova, Bela; Zapotocky, Michal
Abstract: INTRODUCTION: Paediatric high-grade gliomas (HGG) are characterised by the aggressive biological behaviour with dismal prognosis of long-term survival 10-15%. Current molecular-biological diagnostic approaches allow for more precise characterization and determination of new unique subgroups of HGG. Our aim was to identify novel and rare HGG subgroups within our institution cohort. PATIENTS AND METHODS: Our reference centre patients′ cohort consisted of 97 clinically annotated patients with HGG diagnosed between 2000 and 2021. Sanger sequencing was used for screening of the most common HGG-related oncogenic drivers; furthermore we employed whole genome methylation array (Illumina Infinium MethylationEPIC BeadChip) and for selected samples RNA sequencing and expression profiling. RESULTS: Based on H3 status and previous radiotherapy we separated our HGG cases into the RIG, H3mut and H3wt groups. In contrast to H3mut(n=35) and RIG(n=11) that were uniformly fatal, H3wt group contained a proportion of long-term survivors. In the H3wt group we found patients carrying driver mutations in IDH1/2 (n=2) and BRAFV600E (7). Five young patients (under 3) consisted of 3 infant hemispheric gliomas (with NTRK and ROS1 fusions), one gliomatosis cerebri and one brainstem anaplastic astrocytoma with MYB/QKI fusion. We also identified a rare EWSR1-PATZ1 gene fusion in one patient. Importantly, long-term survivors recruited from these subgroups. On the contrary, four cases of MYCN GBM with poor prognosis presented in various locations: one disseminated, one gliomatosis cerebri and two with hemispheric tumour. We identified one patient with "hypermutated" glioblastoma and used targeted therapy with Nivolumab. In three samples of our patients with thalamic glioblastomas, we detected "loss of H3K27-trimethylation" caused by EZHIP overexpression. These tumours proved to be very aggressive with early metastatic recurrence and dismal prognosis. SUMMARY: Detailed characterization of H3 wild-type HGG is very important for further understanding of their biological behaviour, diagnostics, prognostication and identification of therapeutic targets.